2005
DOI: 10.1111/j.1523-1755.2005.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1 is up-regulated in unstressed and stressed HO-1 knockout mice: Pathophysiologic correlates1

Abstract: In the absence of HO-1, expression of MCP-1 is significantly and consistently enhanced in unstressed and stressed conditions. We speculate that the protective effects of HO-1 in injured tissue may involve, at least in part, the capacity of HO-1 to restrain up-regulation of MCP-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 46 publications
8
121
0
1
Order By: Relevance
“…40 In addition, it was demonstrated that whereas basal MCP-1 expression in some tissues, such as heart and bone marrow, was comparable in both HO-1 ϩ/ϩ and HO-1 Ϫ/Ϫ mice, renal and plasma MCP-1 were elevated in unstressed and stressed HO-1 Ϫ/Ϫ mice. 41 In this study, the number of macrophages in the kidneys from the sham-operated group and the CL (right) kidneys did not differ between the two HO-1 genotypes but was significantly higher in the obstructed kidneys of HO-1 Ϫ/Ϫ mice. Interestingly, the amount BASIC RESEARCH www.jasn.org of fibrosis seemed to affect the CL kidneys from HO-1 Ϫ/Ϫ mice more than in the respective kidneys from HO-1 ϩ/ϩ mice, with a trend toward statistical significance (P ϭ 0.07), suggesting a systemic effect of the inflammatory process, perhaps caused by differences in resident and circulating cytokines.…”
Section: Discussionmentioning
confidence: 84%
“…40 In addition, it was demonstrated that whereas basal MCP-1 expression in some tissues, such as heart and bone marrow, was comparable in both HO-1 ϩ/ϩ and HO-1 Ϫ/Ϫ mice, renal and plasma MCP-1 were elevated in unstressed and stressed HO-1 Ϫ/Ϫ mice. 41 In this study, the number of macrophages in the kidneys from the sham-operated group and the CL (right) kidneys did not differ between the two HO-1 genotypes but was significantly higher in the obstructed kidneys of HO-1 Ϫ/Ϫ mice. Interestingly, the amount BASIC RESEARCH www.jasn.org of fibrosis seemed to affect the CL kidneys from HO-1 Ϫ/Ϫ mice more than in the respective kidneys from HO-1 ϩ/ϩ mice, with a trend toward statistical significance (P ϭ 0.07), suggesting a systemic effect of the inflammatory process, perhaps caused by differences in resident and circulating cytokines.…”
Section: Discussionmentioning
confidence: 84%
“…Sustained increases in their levels have been associated with persistent inflammation, neovascularization, and decreased re-epithelialization and tissue repair. 44 -47 The fact that these same chemokines are subjected to down-regulation by either HO-1 induction or supplementation of CO or biliverdin, 21,43,48,49 further underscores the notion that the absence of considerable HO activity promoted the uncontrolled massive production of proinflammatory signals and, consequently, chronic inflammation and neovascularization. This is strongly supported by the demonstration that biliverdin administration rescued the impaired inflammatory and reparative response of the HO-2-null mice; it accelerated wound repair, promoted resolution, and attenuated neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1's downregulation may be due to the glucose effect on HO-1 promoter activity (59) and may cause renal dysfunction (for review, see [40]). HO-1 upregulation decreases inflammatory cytokines (60,61). Bilirubin can scavenge reactive oxygen species (62)(63)(64) and inhibit activation of NADPH oxidase (15) and protein kinase C (16), which are key signaling steps in oxidant-induced vascular injury.…”
Section: Discussionmentioning
confidence: 99%